Perancangan Game Edukasi â€œFish Identityâ€ Dengan Menggunakan JavaTM - Teguh Martono, Kurniawan (Jurnal Sistem Komputer, 2011)
Game is currently experiencing rapid growth. There are so many types of games on the market today, including the types of real time strategy, first person shooter, and role playing game. The development of this game is used by various circles to convey a some message. One of the current games that are often shelled is educational game. â€œFish Identityâ€ one of educational game developed. The game is to introduce of fish species to the students. By using this educational game is expected students to be better in familiar types of fish species that exist. Test for this game using black box testing, is intended to get the functionality of this game which includes navigator key function, target, fishing rod function. Result of the testing is functioning properly